Clinical Evaluation Mustadi Yoga in the Management of Medoroga w.s.r to Hyperlipidemia - Raina, Namartha; sharma, Rajesh (International Research Journal of Ayurveda & Yoga, 2022)
Cholesterol is an important building block in the formation and repair of cell walls, function of nerve tissue, and the production of hormones such as testosterone, estrogen, and the stress hormone, cortisol. It is important to understand that fat tissue (cholesterol) in itself is not bad, and is actually essential for the body to function properly. The mixing of ama with fat tissue is the main cause of imbalanced cholesterol as per Ayurveda. When meda dhatu mixes with ama, it changes the quality of fat tissue and the quality of cholesterol, making it unhealthy rather than healthy. High cholesterol raises our risk for heart disease, heart attack. In Ayurvedic perspective, the production of cholesterol does not necessarily need to be lessened, but it needs to be balanced. When the digestion is balanced and healthy, then the body produces .the right amount of cholesterol, in the right proportion to nourish the body. Balanced diet, proper lifestyles, exercise, yoga, balanced Agni (digestion & metabolism) play important role in prevention of hypercholesterolemia.